The Effect of Investment Opportunity Set, Company Growth, and Debt Covenant on Accounting Conservatism in Consumer Goods Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) 2018-2021 - Mondhi; Wehdawati; Muhammad Zainal Arifin; Adelia Maulida; Fahrina; Muthia Putri Ramadhani Arasy Hasan (International Journal of Economics Accounting and Management, 2025)
A business phenomena that happens in consumer products manufacturing firms like PT Kimia Farma Tbk. and other businesses due to the emergence of conflicts of interest such as cases related to overstated profits. The conflicts that occur can be reduced by applying the principles of accounting conservatism. Agency theory is supported to explain that accounting conservatism is a signal given to avoid a manager's opportunistic behavior when financial reports are presented. The purpose of this study was to determine the effect of debt covenants, business expansion, investment conservative prospects in accounting. Consumer product companies listed on the Indonesia Stock Exchange between 2018 and 2021 represent the target population of this research. which report complete financial reports. The sample selection technique is saturated sample technique. The sample that meets the criteria is 25 companies. Multiple regression analysis serves as the analytical method applied in this research. Hypothesis testing is conducted using version 25.0 of the SPSS software for Windows. Simultaneous test results show that investment opportunity set, company growth, and debt covenants influence accounting conservatism. The results of partial hypothesis testing indicate that investment opportunities yield a significance level of 0.715> 0.050, suggesting that such opportunities do not have a statistically significant influence on accounting conservatism, hence H1 is rejected. H2 is supported as business expansion exerts a negative impact on accounting conservatism (significant value 0.000 < 0.050), and H3 is supported as well since debt covenants are shown to negatively affect accounting conservatism (significant value 0.000 < 0.05)